Beyond the academic milieu: friendship in the shadow of death (studies). (3rd April 2021) - Rotar, Marius; Teodorescu, Adriana
ABSTRACT: This introduction provides some insights on this special issue of Mortality, entitled Dying and Death in Former Communist European Countries, setting the issue against the general background of death studies and, more specifically, of death studies in eastern European countries. Some relevant references to the Dying and Death in 18th-21st Century Europe International Conference, organised in Romania, at the '1 Decembrie 1918ʹ University of Alba Iulia, Romania, between 2007 and 2019, are also made. The rationale and also the limitations of this special issue are brought into attention. The papers that form this issue are briefly presented.